Day ahead scheduling of PHEVs and D-BESSs in the presence of DGs in the distribution system - Jha B.K.; Singh A.; Kumar A.; Dheer D.K.; Singh D.; Misra R.K. (My University, 2025)
The rapid growth of plug-in hybrid electric vehicles (PHEVs)/electric vehicles (EVs) and their capability of providing a vehicle to grid power support in distribution network needs in-depth studies for the effective operation of the distribution system. Charging/discharging of EV from/to the distribution system has significant impacts on the load demand, network congestion, voltage rise/dip, and other operational issues. Power supply from distributed generators (DGs) is utilised during the peak demand hour to avoid the need for upgradation of the distribution systems. In this study, 24-hour day ahead power scheduling of PHEVs (in between arrival and departure time), distributed-battery energy storage system (D-BESS) and DGs is proposed to mitigate its effect on the distribution system. Four objective functions including system operating cost, CO2 emission, energy losses, and load flattening are considered to examine the effect of distributed sources on the 38-bus distribution system. An effective butterfly optimiser is implemented to minimise single weighted objective function. To understand individual as well as combined effect of unscheduled PHEVs charging, scheduled charging/discharging of PHEVs, D-BESS, and DGs various case studies is performed. On the basis of these case studies, optimal scheduling of PHEVs, D-BESS, and DGs are proposed to improve the overall system performance. © The Institution of Engineering and Technology 2019